2020
DOI: 10.3390/vaccines9010003
|View full text |Cite|
|
Sign up to set email alerts
|

Resources, Production Scales and Time Required for Producing RNA Vaccines for the Global Pandemic Demand

Abstract: To overcome pandemics, such as COVID-19, vaccines are urgently needed at very high volumes. Here we assess the techno-economic feasibility of producing RNA vaccines for the demand associated with a global vaccination campaign. Production process performance is assessed for three messenger RNA (mRNA) and one self-amplifying RNA (saRNA) vaccines, all currently under clinical development, as well as for a hypothetical next-generation saRNA vaccine. The impact of key process design and operation uncertainties on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 36 publications
0
87
0
1
Order By: Relevance
“…Preclinical in vitro research on the influenza A virus showed the advantage of optimizing the mRNA sequence with a view to new strain outbreaks [ 100 ], which is also applicable to SARS-CoV-2. Moreover, the strengths of this type of vaccine platform include the fact that it is easily scalable and its low cost of production, making it possible for the supply to meet the demand derived from the pandemic situation [ 101 ]. Additionally, mRNA technology is also being studied for expressing monoclonal antibodies for passive immunotherapy [ 102 ] that could be used in patients with severe clinical manifestations.…”
Section: Vaccines In Clinical Developmentmentioning
confidence: 99%
“…Preclinical in vitro research on the influenza A virus showed the advantage of optimizing the mRNA sequence with a view to new strain outbreaks [ 100 ], which is also applicable to SARS-CoV-2. Moreover, the strengths of this type of vaccine platform include the fact that it is easily scalable and its low cost of production, making it possible for the supply to meet the demand derived from the pandemic situation [ 101 ]. Additionally, mRNA technology is also being studied for expressing monoclonal antibodies for passive immunotherapy [ 102 ] that could be used in patients with severe clinical manifestations.…”
Section: Vaccines In Clinical Developmentmentioning
confidence: 99%
“…Based on the study by Kis [ 92 ], 230,700 kWh of power/y is required to support the production of 69,020 g vaccine/y. The global demand for RNA vaccine was predicted as 1.56 × 10 10 doses, containing 0.1 μg saRNA - 100 μg mRNA/dose [ 93 ].
Fig.
…”
Section: Energy Needs Assessmentmentioning
confidence: 99%
“…The mRNA-LNP platform has several advantages over other vaccination strategies; it can be repeatedly administered without inducing immunologic memory to the delivery vector, has no chance of incorporating into potential oncogenic sites within the genome, is relatively inexpensive to synthesize large quantities compared to recombinant protein production, and can be easily scaled from production in small laboratories to manufacturing facilities for vaccination campaigns [15,16]. The mRNA included in the vaccine formulation is in vitro synthesized to mimic the host mRNA in order to increase mRNA stability and translation efficiency.…”
Section: Rna Vaccine Overviewmentioning
confidence: 99%
“…Reviews which highlight and discuss existing vaccines against specific flaviviruses can be found here; YFV [4], JEV [9], TBEV [10], WNV [11], DENV [12,13], and ZIKV [14]. Reviews which discuss considerations for commercialization and large-scale production of mRNA vaccines can be found here [15,16].…”
Section: Introductionmentioning
confidence: 99%